99mTc-MIBI SPECT/CT imaging had high sensitivity in accurate localization of parathyroids before parathyroidectomy for patients with secondary hyperparathyroidism. (1st January 2019) - Zeng, Ming; Liu, Wei; Zha, Xiaoming; Tang, Shaowen; Liu, Jin; Yang, Guang; Mao, Huijuan; Yu, Xiangbao; Sun, Bin; Zhang, Bo; Ouyang, Chun; Zhang, Lina; et al.
Abstract: Purpose: Accurate preoperative parathyroid localization is important for successful parathyroidectomy (PTX). The aim of our study was to investigate whether SPECT/CT has enhanced effect in preoperative localization of parathyroids. Methods: In our retrospective cohort study, we evaluated the effects of technetium-99m methoxyisobutylisonitrile-single-photon emission computed tomography/computed tomography ( 99m Tc-MIBI SPECT/CT) on preoperative parathyroid localization for 645 secondary hyperparathyroidism (SHPT) patients. Among them, 569 successful PTX patients were divided into group A (received 99m Tc-MIBI scintigraphy, n  = 175) and group B (received 99m Tc-MIBI scintigraphy and SPECT/CT imaging, n  = 394). Sensitivity, specificity, and consistency of two imaging methods in preoperative localization of parathyroids were compared. Results: Overall sensitivity and consistency were higher in group B, while there was no difference in specificity between the two groups. In group A, the sensitivity of 99m Tc-MIBI was 50.00%, 77.11%, 61.76%, and 76.54% in the right upper gland (RU), right lower gland (RL), left upper gland (LU), and left lower gland (LL) subgroups, while the consistency was 52.00%, 76.57%, 61.71%, and 75.43%, respectively. In group B, the sensitivity of 99m Tc-MIBI with SPECT/CT was 69.39%, 90.03%, 78.07%, and 84.27%, and the consistency was 69.54%, 88.32%, 78.43%, and 84.26%, respectively. The sensitivity and consistency in lower glands were higher than in upper glands in both groups. Sensitivity for eutopic parathyroid was higher in group B, while there was no difference for ectopic parathyroid. Conclusions: 99m Tc-MIBI SPECT/CT can increase the sensitivity and consistency of preoperative localization of eutopic parathyroid glands, and it can accurately locate ectopic parathyroid without sensitivity improvement.